Alternative for potassic fertilization of vegetables in organic management in low fertility natural soil of the humid tropics - dos Santos, Aline Moreno Ferreira [UNESP]; dos Santos, Valter Barbosa [UNESP]; de Araújo, Ana Maria Silva; Ferraz Junior, Altamiro Souza de Lima; de Souza Rolim, Glauco [UNESP]; Lazo, Ronald Alvarez; Carvalho, Mary Jane Nunes [UNESP] (Pensoft Publishers, 2020)
The organic food production and mainly the demand for these products have been growing much worldwide, and with this rising demand there is need for more adequate soil management. Organic fertilization is one of the points to improve and the alternative sources of nutrients should be better evaluated. Potassium is an essential nutrient required in large quantities by greenery and fruit, but according to the legislation of organic production, it can only be used as crushed rocks such as potassium sulfate. The objective of this work was to evaluate the efficiency of potassium sulfate (soluble source), wood ash and marble powder as alternative sources of potassium in organic system, using hybrid maize AG 1051 as the indicator crop. The experimental design applied was in randomized blocks in the 3×4×2 factorial scheme, consisting of three potassium sources applied in four doses (0, 60, 90 and 120 kg ha-1 K2O) in the presence and absence of Biofertilizer, with four repetitions. The data were submitted to analysis of variance (ANOVA) and the averages were compared by the Tukey test (p < 0.05). Both wood ash and marble powder tested can be used as complementary potassium fertilization in organic production systems. Marble powder proved to be the most efficient among the treatments and the Biofertilizer did not have a significant effect on the evaluated characteristics.
Keywords: Alternative sources; Biofertilizer; Potassium